Benchmarking Methodology of Banks Based on Financial Sustainability Using CRITIC and RAFSI Techniques - Ali, Jaber; Naser Hussain, Khansaa; Alnoor, Alhamzah; Muhsen, Yousif Raad; Atiyah, Abbas Gatea (Decision Making: Applications in Management and Engineering, 2024)
This study aims to determine the influence of financial risks on the financial sustainability of Iraq banks, in contrast considering the moderator role of financial expertise and the risk of directors’ riskiest directorships. Moreover, the investment attractiveness has also been accounted for specifying the mediating impact between the moderator variables and financial sustainability. Robust random effect model was employed to investigate the determinants of financial sustainability for the listed banks on the Iraqi stock trade and the Iraqi financial marketplace. In addition, multicriteria decision-making techniques were utilized to rank the banks from the best to worst based on financial sustainability. This study has examined 19 Iraqi banks over 14 years from 2007 to 2020 (266 observations), during the development of the Iraqi corporate governance cod. The findings indicate that financial risk has a negative influence on the financial sustainability of Iraq. Furthermore, the link between financial risks and financial sustainability is fully mediated by investment attractiveness. In this context, financial expertise and the relinquishing of directors’ riskiest directorships have an interactive role in the link among investment attractiveness and financial sustainability indicators. Multi-criteria decision making (MCDM) results revealed that the best bank in terms of financial sustainability is BTRI and the worst bank is BNOR. The findings enable managers to develop strategies to mitigate financial risk in phases and prepare for future unpredicted risks. Hence, the results provided an insight to practitioners regarding the best banks in terms of financial sustainability in order to invest and deal with them.